How Long, Narrowly Constructed Wetlands Purify Irrigation Return Water: A Case Study of Ulansuhai Lake, China - Xufeng Mao; Donghai Yuan; Liansheng He; Xiaoyan Wei; Qiong Chen; Libo Bian; Junqi Li (Advances in Meteorology)
The use of constructed wetlands (CWs) in the treatment of raw wastewater in China has proved to be very successful in recent decades. However, it is not known whether surface-flow constructed wetlands can effectively purify irrigation return water. To investigate the performance of a constructed wetland in terms of meeting the goals of pollutant purification, the 8th drainage of Ulansuhai Lake was used for this study. Pollutant removal performances, as well as hydrological characteristic variations in relation to specific characteristics of plants, were investigated utilizing two years of monthly average data. The results indicated that surface-flow constructed wetlands can effectively change the physical characteristics of return water and lead to a sharp decrease in pollutant concentrations. The 1200 m long, narrowly constructed wetland resulted in the average reduction rates of total nitrogen (TN) and total phosphorus (TP) of up to 22.1% and 21.5%, respectively. The overall purification efficient of the constructed wetland presented seasonal variations in four different monitoring periods (May, July, September, and November). Constructed wetlands with multiple types of plants exhibited higher efficiencies in pollutants removal than those with a single type of plant. The current study can provide meaningful information for the treatment of agricultural wastewater.